2011
DOI: 10.1002/ijc.25494
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐beta‐induced protein secreted by peritoneal cells increases the metastatic potential of ovarian cancer cells

Abstract: Ovarian cancer metastasis is characterized by the shedding of malignant cells from the surface of the ovary and their implantation onto the peritoneal surface, which lines the abdominal cavity. As the factors promoting this process are poorly understood, we investigated the ovarian cancer–peritoneal interaction by means of in vitro coculture experiments with ovarian cancer (OVCAR‐5 and SKOV‐3) and peritoneal (LP‐9) cells. One of the proteins differentially expressed in the coculture secretome was identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
90
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 48 publications
(70 reference statements)
9
90
0
Order By: Relevance
“…The highest TGFB1 expression was observed in the MES subtype, and increased TGFBI expression in this subtype was associated with both reduced OS (P = 0.0038, HR = 1.40, 95% CI: 1.11-1.75) and DFS (P = 0.0003, HR = 1.50, 95% CI: 1.21-1.87). We have shown TGFBI to be abundantly expressed by peritoneal cells, and recombinant TGFBI increased the metastatic potential of ovarian cancer cells by promoting cell motility, invasion and adhesion to peritoneal cells (Ween et al 2010). Together these findings support the tumourpromoting role of TGFBI.…”
Section: Role Of Tgfbi In Ovarian Cancersupporting
confidence: 67%
See 2 more Smart Citations
“…The highest TGFB1 expression was observed in the MES subtype, and increased TGFBI expression in this subtype was associated with both reduced OS (P = 0.0038, HR = 1.40, 95% CI: 1.11-1.75) and DFS (P = 0.0003, HR = 1.50, 95% CI: 1.21-1.87). We have shown TGFBI to be abundantly expressed by peritoneal cells, and recombinant TGFBI increased the metastatic potential of ovarian cancer cells by promoting cell motility, invasion and adhesion to peritoneal cells (Ween et al 2010). Together these findings support the tumourpromoting role of TGFBI.…”
Section: Role Of Tgfbi In Ovarian Cancersupporting
confidence: 67%
“…Studies have shown that the level of TGFBI in ovarian cancer tissues is predictive of the disease response to the treatment with the aromatase inhibitor letrozole (Walker et al 2007) or the chemotherapeutic drug paclitaxel (Ahmed et al 2007). Our previous findings suggest that TGFBI is downregulated in ovarian cancer and that high concentration of TGFBI induced ovarian cancer cell death, which supports a tumour suppressor role (Ween et al 2010).…”
Section: Role Of Tgfbi In Ovarian Cancermentioning
confidence: 64%
See 1 more Smart Citation
“…These studies have led to the identification of several proteins that are mechanistically involved in the peritoneal spread of ovarian cancer and may serve as novel ovarian cancer biomarkers and/or therapeutic targets. Studies with Ph.D. students Noor Lokman and Miranda Ween identified a key link between the annexin A2 signalling pathway and activation of the plasminogen-plasmin system (Ween et al 2011b, Lokman et al 2013, Ricciardelli et al 2015. Our findings, together with published literature, support the notion that ECM processing via the plasminogenplasmin pathway promotes the colonisation and attachment of ovarian cancer cells to the peritoneum and actively contributes to the early stages of ovarian cancer metastasis.…”
Section: :11supporting
confidence: 78%
“…Considering the role of coagulation factors in HSPC mobilization and niche-interactions, it is of interest that BIGH3 is cleaved by plasmin 189 and contains a vitamin-K-dependent gamma-carboxylation site, only prevalent in proteins that are involved in coagulation pathways. 190 Moreover, BIGH3 stimulates thrombus formation by activation of platelets, suggesting that it contributes to stabilization of blood clots, whereas its proteolysis by plasmin may contribute to the resolution of clots and to HSPC homeostasis.…”
mentioning
confidence: 99%